A comparative pilot study on Gram-negative bacteria contaminating the hands of children living in urban and rural areas of Indonesia versus Germany – A suitable monitoring strategy for diarrhea risk assessment? - Simanjuntak, Debi Frina; Kusumawati, R. Lia; Bader, Oliver; Lüder, Carsten G. K.; Zimmermann, Ortrud; Groß, Uwe (Frontiers in Microbiology, 2023)
Diarrhea is the second leading cause of death mainly effecting young children. Often it is the result of fecal-oral pathogen transmission. We aimed to investigate whether monitoring the prevalence of Gram-negative bacteria on the hands of asymptomatic children is suitable as an indicator of fecal contamination of the environment in their playground. We compared the prevalence of Gram-negative bacteria on the hands of children, who live in the German city of Göttingen, an urban area in a high-income country, with the situation in Medan as an urban area and Siberut as a rural area both in the middle-income country Indonesia. 511 children at the age of 3 months to 14 years were asked to put their thumb print on MacConkey agar, which was used to screen for the presence of Gram-negative bacteria. These were subsequently identified by using MALD-TOF mass spectrometry and classified into the order Enterobacteriales, Pseudomonadales and others. The highest burden of hand contamination was found in children from rural Siberut (66.7%) followed by children from urban Medan (53.9%) and from urban Göttingen (40.6%). In all three study sites, hand contamination was lower in the youngest (<1 year) and oldest age groups (10-14 years) and highest in the age group 5-9 years. Bacteria of the order Enterobacteriales possibly indicating fecal contamination were most prevalent in Siberut (85.1%) followed by Medan (62.9%) and Göttingen (21.5%). Most facultative and obligate gastrointestinal pathogens such as Escherichia coli (n=2) and Providencia rettgeri (n=7), both being members of the order Enterobacteriales, as well as Aeromonas caviae (n=5), and Vibrio cholerae (n=1) both belonging to other orders were nearly exclusively identified on the hands of children in Siberut. This result was not surprising, because hygienic conditions were lowest in Siberut. Only one isolate of A. caviae was found in Medan, and no facultative gastrointestinal pathogen was identified on the hands of children from Göttingen. Our pilot study therefore indicates that investigating hands of children for the prevalence of Gram-negative bacteria using selective media are a helpful method to monitor hygienic conditions, and thereby assess the risk for diarrhea-causing bacterial pathogens in the environment.